Pilot production of highly efficient metal catalyzed textured diamond wire sawn mc-Si solar cells combined with nickel-copper plated front contact processing. (September 2017) - Pysch, D.; Bay, N.; Burschik, J.; Dümpelfeld, W.; Kühnlein, H.; Lee, B.; Letize, A.; Passig, M.; Qu, X.; Sieber, M.; Vosteen, K.
Abstract: This paper presents first results of combining two promising future technologies: i) metal catalyzed textured diamond-wire sawn (DWS) mc-Si wafers and ii) nickel-copper-silver (Ni/CuAg) plated front contact processing. Results of first optimizations of laser patterning, annealing and module string soldering are presented. A 60-cell module with a power output of 266 W was successfully manufactured. The pseudo fill-factor (pFF) has been identified as the parameter with the highest potential for further improvements. A very promising approach is moving from an emitter profile that is mainly adapted to silver paste properties to an optimized emitter profile for Ni/Cu/Ag-plated contacts. The idea is to reduce the surface doping concentration (reduces Auger recombination) and increase the junction depth (increased pFF and FF).